IMPLEMENTASI TRILOGI SANTRI DALAM MENUMBUHKAN KESADARAN BERBANGSA DAN BERNEGARA DI PONDOK PESANTREN NURUL JADID PAITON PROBOLINGGO - Shalihah, Havivatus; Tohet, Moch (Universitas Islam Negeri Alauddin Makassar, 2020)
Changes that occur due to globalization affect the entire existing order, an era that will not be separated from the negative and positive elements. One of them is the influence of young people on things that are not good, as well as on morals and attitudes of human behavior. Through education, especially pesantren education, the government seeks to fortify young people with role models of life in the nation and state. This study aims to explain the role of the Santri Trilogy in fostering national and state awareness of the students of the Nurul Jadid Paiton Probolinggo boarding school. This research uses descriptive qualitative approach type case study method. Based on the results of the study, it is known that several important points in fostering national and state awareness are through the cultivation of habits in daily life in the form of making mandates mandatory, obeying pesantren regulations, and mutual cooperation. And the efforts made by the government through instilling national and state awareness, being involved in state activities, and holding national seminars.